The Sultan’s Syllabus Revisited: Sixteenth-Century Ottoman Madrasa Libraries and the Question of Canonization - Şen, A. Tunç (Studia Islamica, 2021)
Abstract This study revisits the question of the early modern Ottoman madrasa curriculum, which, ever since the famous Studia Islamica article of Nenad Filipovic and the late Shahab Ahmed in 2004, has come to be recognized as the “sultan’s syllabus,” implying a strict imposition of a centrally-designed course of study. By utilizing a host of endowment lists, book registers, and autobiographical writings of high- to low-ranking Ottoman scholars from the sixteenth century that escaped Ahmed’s and Filipovic’s attention, I aim to redress an argument that was based on a misinterpretation of a single document but has been extensively cited and recycled since its first articulation almost two decades ago. All of these sources, some of which have never or only partially received scholarly attention, shed more accurate light, not only on the scope of learning, teaching, and canon formation in the early modern Ottoman world of scholarship but also on the mediating role the Ottoman court played by supplying copies of books wherever and whenever needed.